2013
DOI: 10.1371/journal.pone.0076548
|View full text |Cite
|
Sign up to set email alerts
|

Do Biopesticides Affect the Demographic Traits of a Parasitoid Wasp and Its Biocontrol Services through Sublethal Effects?

Abstract: Pesticide risk assessments are usually based on short-term acute toxicity tests, while longer-term population dynamic related traits, critical to the success of biological control and Integrated Pest Management (IPM) programs, are often overlooked. This is increasingly important with respect to new biopesticides that frequently cause no short-term acute effects, but that can induce multiple physiological and behavioral sublethal effects, leading to a decrease in population growth and ecosystem services. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
181
2
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(194 citation statements)
references
References 64 publications
5
181
2
6
Order By: Relevance
“…For instance, many active compounds, including abamectin, spinosad, indoxacarb (Siqueira et al 2001;Campos et al 2015); deltamethrin, methamidophos (Lietti et al 2005); and cypermethrin, chlorpyriphos (Roditakis et al 2013), induce the emergence of resistant pest populations. Moreover, these insecticides also negatively impact the natural enemy populations of T. absoluta (Arnó and Gabarra 2011;Biondi et al 2013;Abbes et al 2015) owing to multiple potential side effects as described by Desneux et al (2007) in a review. The effectiveness of biological control using entomopathogenic organisms (González-Cabrera et al 2011;Ben Khedher et al 2015) beneficial insects (Ferracini et al 2012;Chailleux et al 2012;Chailleux et al 2013;Öztemiz 2013;Salehi et al 2016) present valuable alternative methods to synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many active compounds, including abamectin, spinosad, indoxacarb (Siqueira et al 2001;Campos et al 2015); deltamethrin, methamidophos (Lietti et al 2005); and cypermethrin, chlorpyriphos (Roditakis et al 2013), induce the emergence of resistant pest populations. Moreover, these insecticides also negatively impact the natural enemy populations of T. absoluta (Arnó and Gabarra 2011;Biondi et al 2013;Abbes et al 2015) owing to multiple potential side effects as described by Desneux et al (2007) in a review. The effectiveness of biological control using entomopathogenic organisms (González-Cabrera et al 2011;Ben Khedher et al 2015) beneficial insects (Ferracini et al 2012;Chailleux et al 2012;Chailleux et al 2013;Öztemiz 2013;Salehi et al 2016) present valuable alternative methods to synthetic pesticides.…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, one arises, the response of the exotic parasitoid to the portfolio of available pesticides for each crop. The assessment of acute toxicity of pesticides constitute a corner stone for CBC programmes within and IPM programme, as the degree of toxicity of a pesticide could reduce the establishment and survival of non-target arthropods (Jerraya, 2003;Suma et al, 2009;Urbaneja et al, 2009;Biondi et al, 2012aBiondi et al, , 2013Biondi et al, , 2015Juan-Blasco et al, 2013;Vanaclocha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, research has shown that seed treatments may also pose a risk to beneficial organisms via less obvious routes of exposure, causing both lethal and sublethal effects (Li et al 2012). Sublethal effects, in particular, are easily overlooked and yet may have considerable impact on natural enemy population dynamics and the level of ecosystem services contributed by these insects (Desneux et al 2007;He et al 2012;Biondi et al 2012a;Biondi et al 2013;Planes et al 2013) Systemic insecticides are characterized by low lipophilicity, typically exhibiting an octanol-water partition coefficient (log Poct) below 40 (Cloyd and Bethke 2011) which facilitates their translocation in plant tissues. Residues of such insecticides can be translocated to various plant parts (Dively and Kamel 2012;Goulson 2013).…”
mentioning
confidence: 99%